Muraqabah intensification therapy (MIT): an alternative Islamic therapy for social media addiction - Winda Sri Harianti; Rafifah Huwaida; Nindya Sekar Adriwiguna; Hazhira Qudsyi (Intelektual Pustaka Media Utama, 2022)
This era has been witnessing an increasing sophistication in the technological development, which had an impact on people’s quality of life. For instance, many kinds of currently evolving social media ease mutual communication and interaction among individuals. Nevertheless, there has been an increasing concern over the usage of social media given its excessive use and its adverse impacts. Some evidences of excessive social media usage share some similar indicators categorized into behavioral addiction. This phenomenon is increasingly alarming because technological development is inseparable from human life. Nowadays, there have been many methods offered to overcome social media addiction. Accordingly, the purpose of this study is to examine muraqabah concept as a spiritual intervention based on Islamic tenet to overcome addictive behavior using a integrative literature review from previous empirical studies that have been conducted in Indonesian and English both in qualitative and quantitative methods. The result from previous study has been proven that daily practical of muraqabah can manage the primary psychological aspects of humans. Therefore, spiritual intervention is evident to increase human psychological, social, spiritual, physical health, and individual’s self-actualization, which makes this therapy model as an effective and alternative way to cope with social media addiction and prevent a possibility of relapse behavior.